THE RELATIONSHIP BETWEEN GADGET ADDICTION AND STUDENTS' MENTAL HEALTH: AN ISLAMIC EDUCATIONAL PERSPECTIVE - Muhammad Ridwan Hakim; Nurul Izzah (Universitas Islam Depok, 2025)
This study aims to analyze the relationship between gadget addiction and students' mental health from the perspective of Islamic education. Gadget addiction has become a serious concern among Indonesian students, with demonstrable impacts on multiple dimensions of mental health, including anxiety, depression, sleep disorders, and impaired cognitive functioning. Employing a mixed-methods approach quantitative correlational and qualitative library research the study integrates empirical data analysis (n=284 senior high school students in three major Indonesian cities) with theoretical examination based on Nicholas Carr's The Shallows: What the Internet Is Doing to Our Brains and Islamic educational psychology. Results demonstrate: (1) a significant positive correlation between gadget addiction and anxiety levels (r=0.71, p<0.001) and depression (r=0.64, p<0.001); (2) a negative correlation between gadget addiction and sleep quality (r=-0.68, p<0.001) and academic achievement (r=-0.59, p<0.001); (3) the Islamic perspective identifies gadget addiction as a form of israf (wastefulness) and ghafla (heedlessness), which contradicts the principle of al-'aql (intellect) as a divine trust (amanah) that must be preserved. An intervention model grounded in Islamic Counseling and Guidance (BKI) with a tazkiyatun nafs approach is proposed as a comprehensive solution for addressing gadget addiction among Muslim students.